1991
DOI: 10.1128/jvi.65.11.5702-5709.1991
|View full text |Cite
|
Sign up to set email alerts
|

cDNA sequence and genomic characterization of intracisternal A-particle-related retroviral elements containing an envelope gene

Abstract: Intracisternal A-particle retrotransposons (IAPs) are retroviruslike elements that are defective in envelope protein synthesis and exist without an extracellular stage. We have isolated a novel class of cDNAs that are related to known IAP elements in the nucleotide and deduced protein sequence of gag and pol genes but also contain a previously unidentified reading frame between the pol gene and putative U3 region. Analysis of the deduced protein sequence reveals features of the putative protein that are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
(41 reference statements)
2
31
0
Order By: Relevance
“…The elements from Eker rat-associated IAP (ERA-IAP), IAPE-Y, IAPE-1, and the woodchuck were PCR amplified. The IAPE-1-related elements (elements 3, 4, 8, 10, 16, 17, and 18) were amplified from genomic DNA isolated from AtT-20 cell line (ATTC CCL-89), using primers (nt 3449 to 3466 and 3635 to 3654) derived from the IAPE-1 cDNA sequence (35). The elements were introduced into pR(Ϫ)Rev(Ϫ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The elements from Eker rat-associated IAP (ERA-IAP), IAPE-Y, IAPE-1, and the woodchuck were PCR amplified. The IAPE-1-related elements (elements 3, 4, 8, 10, 16, 17, and 18) were amplified from genomic DNA isolated from AtT-20 cell line (ATTC CCL-89), using primers (nt 3449 to 3466 and 3635 to 3654) derived from the IAPE-1 cDNA sequence (35). The elements were introduced into pR(Ϫ)Rev(Ϫ).…”
Section: Methodsmentioning
confidence: 99%
“…This search revealed that in addition to the CTEs, such elements are also present in several previously identified IAPs, such as the murine IAPE-1 (35) and IAPE-Y (GenBank accession number X87638) and the rat ERA-IAP (46). Sequence alignment of these elements shows that the homology to CTE IAP (and SRV-1 CTE) is mostly confined to the internal loop regions (Fig.…”
Section: Fig 3 the Newly Identified Cte Is Part Of An Iap Inserted mentioning
confidence: 96%
See 1 more Smart Citation
“…The intracisternal-A-particle-related envelope-encoding (IAPE) group of retroviral elements in Mus musculus contains a reading frame with close resemblance to retroviral env genes (17). IAPE transcripts include a 2.8-kb spliced subgenomic env mRNA.…”
mentioning
confidence: 99%
“…The 7.5-kb IAPE subgroup (IAPE-A) potentially represents intact IAPE proviruses whereas the smaller (4.0-kb [IAPE-B] and 3.7-kb [IAPE-C]) elements have been shown to lack large parts of the gag and pol genes. Each of these subgroups consists of approximately 30 to 50 proviral elements (17). A number of IAPE elements differ in size from the types described above and may represent either proviruses with less common truncations or restriction site polymorphisms.…”
mentioning
confidence: 99%